Artists in the city: exploring the creative identities of visual artists in Dhaka - Joyeeta, Sumaiya Shams (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Social Science in Anthropology, 2023.